Time to cranial computerised tomography for acute traumatic brain injury in paediatric patients: Effect of the shorter stays in emergency departments target in New Zealand. (13th April 2017) - Jones, Peter G; Kool, Bridget; Dalziel, Stuart; Shepherd, Michael; Le Fevre, James; Harper, Alana; Wells, Susan; Stewart, Joanna; Curtis, Elana; Reid, Papaarangi; Ameratunga, Shanthi
Abstract : Aim: Timely access to computerised tomography (CT) for acute traumatic brain injuries (TBIs) facilitates rapid diagnosis and surgical intervention. In 2009, New Zealand introduced a mandatory target for emergency department (ED) stay such that 95% of patients should leave ED within 6 h of arrival. This study investigated whether this target influenced the timeliness of cranial CT scanning in children who presented to ED with acute TBI. Methods: We retrospectively reviewed a random sample of charts of children <15 years with acute TBI from 2006 to 2012. Cases were identified using International Classification of Disease 10 codes consistent with TBI. General linear models investigated changes in time to CT and other indicators before and after the shorter stays in ED target was introduced in 2009. Results: Among the 190 cases eligible for study ( n  = 91 pre‐target and n  = 99 post‐target), no significant difference was found in time to CT scan pre‐ and post‐target: least squares mean (LSM) with 95% confidence interval = 68 (56–81) versus 65 (53–78) min, respectively, P  = 0.66. Time to neurosurgery (LSM 8.7 (5–15) vs. 5.1 (2.6–9.9) h, P  = 0.19, or hospital length of stay (LSM: 4.9 (3.9–6.3) vs. 5.2 (4.1–6.7) days, P  = 0.69) did not change significantly. However, ED length of stay decreased by 45 min in the post‐target period (LSM = 211 (187–238) vs. 166 (98–160) min, P  = 0.006). Conclusion: Implementation of the shorter stays in ED target was not associated with a change in the time to CT for children presenting with acute TBI, but an overall reduction in the time spent in ED was apparent.